Hubungan Antara Kebutuhan Berprestasi, Harga Diri, Lokus Kendali, Kebiasaan Belajar, dan Lingkungan Belajar Dengan Prestasi Akademik Mahasiswa - Muhid, Abdul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2018)
This study wants to look at the factors of personality characteristics and external factors such as the learning environment which correlates with the academic achievement of the students granted the “Bidik Misi” scholarship of UIN Sunan Ampel Surabaya. Three things want to be known in this study; (1) identify the propensity of need for achievement, self-esteem, locus of control, learning habit and environment, and the propensity of the students granted “Bidik Misi” scholarship; (2) the correlation and contribution between need for achievement, self-esteem, locus of control, learning habit and environment (either individually or jointly) and academic achievement of the students granted “Bidik Misi” scholarship; and (3) which factors are the most efficient of the five factors (need for achievement, self-esteem, locus of control, and learning habit and environment) toward academic achievement of the students granted “Bidik Misi” scholarship. This study found the average propensity of academic achievement of the students granted “The Bidik Misi” scholarship is as high as the average GPA of 3.53; the propensity of achievement needs of the students granted ‘The Bidik Misi scholarship is very high; the propensity of self-esteem of the students granted “Bidik Misi” scholarship is very high; the propensity of locus of control of the students granted “Bidik Misi” scholarship is very high; the propensity of learning habit of the students granted “Bidik Misi” scholarship is very high; and the propensity of perception of the students granted “Bidik Misi” scholarship to the learning environment is very positive. This study also proves that there is a significant correlation between the need for achievement, self-esteem, locus of control, learning habit and environment, and academic achievement of the students granted the “Bidik Misi” scholarship. There is a significant positive correlation between the need for achievement and academic achievement of the students granted “Bidik Misi” scholarship. There is no significant correlation between self-esteem and academic achievement of the students granted “Bidik Misi” scholarship. There is no significant correlation between locus of control and academic achievement of ‘the students granted the “Bidik Misi” scholarship. There is no significant correlation between learning habits and academic achievement of the students granted “Bidik Misi” scholarship. There is no significant correlation between the learning environment and academic achievement of the students granted the “Bidik Misi” scholarship. The most efficient factor of the five factors (need for achievement, self-esteem, locus of control, learning habit, and environment) toward the academic achievement of the students granted the “Bidik Misi” scholarship is the achievement need factor. It was proved that the effective contribution (SE) of the achievement needs variable is significantly higher than the effective contribution (SE) of other variables such as self-esteem, locus of control, learning habit, and environment. Keywords: need for achievement, self-esteem, locus of control, learning habit and environment, academic achievement, and the students granted “Bidik Misi” scholarship.